Shear resistance of steel fiber-reinforced concrete beams without conventional shear reinforcement on the basis of the critical shear band concept. (1st August 2018) - Tung, Nguyen Duc; Tue, Nguyen Viet
Highlights: An extension of the shear band concept to estimate the shear capacity of SFRC beams is presented. Stress states in the shear span of SFRC beams are analyzed. Effects of steel fibers on the flexural and shear cracking characteristics are investigated. Comparison to the observed shear resistance of a large set of available test data is provided. Abstract: Recently, a concept to estimate the shear capacity of slender reinforced concrete beams without stirrups by examining the principal tensile stress within the shear span was introduced. Considering the existence of both the concrete normal stress and the shear stress in the tension zone, the calculated principal tensile stress is in excess of the concrete tensile strength in a narrow band in this concept. In this band, damage in form of micro-cracking is assumed. The critical shear crack is formed by coalescence of micro-cracks when the damaged band reaches a critical size. By limiting the tensile cracking in the shear band, steel fibers can postpone the critical shear crack development and, thus, enhance the shear resistance in this concept. This paper presents an extension of this method to estimate the shear capacity of slender steel fiber-reinforced concrete beams without conventional shear reinforcement. The proposed method is shown to properly estimate the shear resistance of a large set of available test data, being able to account for most influencing parameters.